2020
DOI: 10.1136/bmjopen-2019-034617
|View full text |Cite
|
Sign up to set email alerts
|

Patient safety in ambulatory care from the patient's perspective: a retrospective, representative telephone survey

Abstract: ObjectivesData on patient safety problems (PSPs) in ambulatory care are scarce. The aim of the study was to record the frequency, type, severity and point of origin of PSPs in ambulatory care in Germany.DesignRetrospective cross-sectional study.SettingComputer-assisted telephone interviews with randomly recruited citizens aged ≥40 years in Germany who were asked about their experiences with PSPs in ambulatory care.Participants10 037 citizens ≥40 years.MeasuresA new questionnaire was developed to record patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 17 publications
0
17
0
3
Order By: Relevance
“…The excellent response rate of this study indicates a high willingness of patients to provide feedback on their care if the response burden is acceptable, one factor for this being the length of the questionnaire [ 55 ]. Other surveys of patient experience with patient safety in ambulatory care using longer questionnaires yielded response rates of 12%, 18% and 64% in a telephone survey [ 3 ], a mailed survey [ 4 ] and a waiting room survey [ 6 ] respectively. Giles et al [ 27 ] point out that conducting on site surveys with long questionnaires face the challenge that the time to complete and return the questionnaire maybe longer than the waiting time and that completion may be interrupted by being called in to the doctor.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The excellent response rate of this study indicates a high willingness of patients to provide feedback on their care if the response burden is acceptable, one factor for this being the length of the questionnaire [ 55 ]. Other surveys of patient experience with patient safety in ambulatory care using longer questionnaires yielded response rates of 12%, 18% and 64% in a telephone survey [ 3 ], a mailed survey [ 4 ] and a waiting room survey [ 6 ] respectively. Giles et al [ 27 ] point out that conducting on site surveys with long questionnaires face the challenge that the time to complete and return the questionnaire maybe longer than the waiting time and that completion may be interrupted by being called in to the doctor.…”
Section: Discussionmentioning
confidence: 99%
“…The included studies were heterogeneous in terms of definition and measurement of patient safety incidents which may partly explain the substantial range. However, when looking only at studies based on patient reports, the variation in observed rates remains considerable with 8 to 45% of participants reporting having experienced a patient safety problem [ 3 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…With a 1-year incidence of 14.2%, ambulatory care patients aged ≥40 years in Germany frequently report self-experienced patient safety problems (PSP). 1 Internationally, the state of research on the frequency of PSP in the ambulatory care sector is insufficient. According to a systematic literature review by Panesar et al 1-24 patient safety incidents (PSI) per 100 000 ambulatory consultations can be expected.…”
Section: Introductionmentioning
confidence: 99%